A game‐based incentive model for service cooperation in VANETs. (21st July 2014) - Mao, Yuxin; Zhu, Ping; Wei, Guiyi; Hassan, Mohammad Mehedi; Hossain, M. Anwar
Summary: Because of the highly dynamic topology and the unstable service status of nodes, services in vehicular ad hoc networks (VANETs) are not always reliable enough for users. Nodes in such a VANET incline to be selfish, which will even enhance this situation. In this work, we present an incentive model for VANETs to support more reliable services in network. We model the situation of service request and response in VANETs by using game theory. We consider the competitive and cooperative relationship between the nodes to formulate the game for VANETs. A contribution measurement is given in order to encourage cooperation during the game. Nodes are encouraged to provide more services to their neighbors in order to acquire more services from other nodes in our model. We also conduct a simulation for the proposed model and give detailed analysis in this work. From the results of the simulation, we argue that we could enable a VANET to support more reliable service by configuring suitable parameters for it. Copyright © 2014 John Wiley & Sons, Ltd.